Identification of Risk Factors for Late-Onset Neonatal Sepsis in Post-Operative Neonates - Aslam, Hasnain; Ahmed, Usman; Sardar, Zainab; Qamar, Muhammad Salman; Chaudhry, Ali Raza; Sabir, Fareeba; Gondal, Mudassar Fiaz (Journal of Neonatal Surgery, 2025)
Introduction:Defined As The Systemic Condition That Arises From Viral, Bacterial Or Fungal Etiology, Associated With Hemodynamic Changes And Clinical Findings, Sepsis Is One Of The Most Common Causes Of Neonatal Mortality And Morbidity. Various Preventable Risk Factors Are Associated With The Developed Of Late-Onset Sepsis In Neonates. The Problem Of Neonatal Sepsis, Especially In Post-Op Neonates In Low-Income Countries Is Plagued By A Scarcity Of Research. Conducted In The Hdu Of Pediatric Surgery Department Of Holy Family Hospital, This Longitudinal Study Is Part Of The Quality Improvement Project To Improve Neonatal Outcomes. Objectives:This Study Aims To Identify The Risk Factors Associated With Late-Onset Sepsis In Post-Op Neonates In The Hdu Of Paeds Surgery Department Of Holy Family Hospital, A Tertiary Care Hospital In Punjab, Pakistan. In Addition To Risk Factors Already Elaborated By Previous Studies, This Study Also Aims To Delineate Additional Risk Factors Associated With Sepsis In The Context Of Post-Op Setups I.E. Fever Prior To Surgery, General Hygienic Measures Observed By The Attendants And Doctors And Severity Of Surgical Wounds. Methods:In Compliance With The Guidelines Issued By The Ethical Board, A Prospective Observational Study Recruiting 91 Neonates Was Carried Out For 6 Months From June, 2022 To December,2022. Periodic Evaluation Was Carried Out Using Standardized Checklists Which Recorded The Possible Predictor Variables I.E. Birth Weight, Severity Of Surgical Wounds, General Hygienic Practices, Fever Prior To Surgery And Duration Of Iv Catheterization. Data Obtained Was Subject To Multivariate Logistic Regression Using Spss V23. Results:Sepsis Was Prevalent In 34 (37.4%) Post-Op Neonates. Low Birth Weight [Or 3.08 95% Ci (1.12-8.47) And Fever Prior To Surgery [Or 2.79 95% Ci (1.03-7.55)] Were Found To Be Statistically Significant Factors Contributing To Neonatal Sepsis, Whereas The Study Of General Hygienic Practices, Severity Of Surgical Wounds And Duration Of Iv Catheterization Failed To Yield Statistically Significant Results, Possibly Owing To Small Sample Size. Conclusion:Further Studies Employing A Larger Sample Size Are Mandated In Order To Establish The Association Of The Aforementioned Risk Factors For Neonatal Sepsis. Low Birth Weight Neonates And Those With Fever Prior To Invasive Procedures Require Rigorous Monitoring For The Prompt Diagnosis And Prevention Of The Complications Associated With Neonatal Sepsis